Teachers' Attitudes Toward Tablet Integration in Teaching: Evidence from Public Primary Schools in Ubungo Municipality, DSM, Tanzania - Agness B Mafuja; Prospery M Mwila (PT. Pusmedia Group Indonesia, 2026)
The integration of digital technologies, particularly tablets, into primary education has become a key focus of educational reform in Tanzania. Despite government efforts to promote Information and Communication Technologies (ICT) in schools, the effective use of tablets in classroom instruction remains limited. This study examined teachers’ attitudes toward tablet integration in teaching in public primary schools in Ubungo Municipality, Dar es Salaam, Tanzania.The study employed a mixed-methods approach using a convergent parallel research design. Data were collected from 56 participants, including teachers, headteachers, ICT coordinators, and pupils, through questionnaires, interviews, and classroom observations. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed thematically. The findings showed that teachers’ attitudes toward tablet integration were generally undecided, with an overall mean score of 2.80 on a five-point scale. Teachers demonstrated limited confidence in using tablets during lessons (M = 2.25) but expressed a strong need for further ICT training (M = 4.38). Teachers were uncertain about the usefulness of tablets in improving teaching (M = 3.13) and enhancing lesson engagement (M = 3.25). Pupils’ responses confirmed limited classroom use, with 70.0% (28 out of 40 pupils) reporting that teachers did not use tablets during lessons (M = 2.20). Classroom observations further revealed that tablets were not integrated into any observed lessons. The study concludes that teachers’ willingness to adopt tablets is constrained by inadequate pedagogical skills, limited training opportunities, weak technical support, unreliable electricity, poor internet connectivity, and insufficient functional devices. Effective tablet integration requires sustained professional development, improved ICT infrastructure, and supportive school leadership.